The Bos Funds Uses Analysis In High Schools During The Pandemic Period In Palopo City - Tsabita Nanda Yusuf, Yusfi; Haliah, Haliah; Nirwana, Nirwana (International Journal of Educational Research & Social Sciences, 2023)
This study aims to determine the use of BOS funds in high school during the pandemic in Palopo City. The variable of this research is the use of BOS funds for senior high schools in Palopo City by trying to analyze the use of BOS Funds during the pandemic based on the 12 components of the use of BOS Funds in accordance with Permendikbud Number 6 of 2021 concerning Technical Guidelines for the Management of School Operational Assistance Funds. The population of this research is high school in Palopo City, while the sampling in this study uses purposive sampling technique. The sample in this study amounted to 4 (four) senior high schools in Palopo City. The data was collected by using observation, interview, and documentation techniques, the research method used descriptive qualitative. The results showed that: The use of high school BOS funds in Palopo City during the pandemic was in accordance with Permendikbud Number 6 of 2021, there was no use that was not in accordance with existing regulations. The usage that experienced the largest growth was for Honor Payments, while the usage that experienced the largest decline was for the Implementation of Learning and Extracurricular Activities.